Postlitteraten og den genfundne begejstring: Om at nyde den gode litteratur på arbejdet - Nyegaard, Ole (Passage - Tidsskrift for litteratur og kritik, 2020)
The article discusses audiobooks from the listener’s perspective and examines how the circumstances under which you listen determine which types of audiobooks suit you best; how audiobooks affect works of literature; and how the good audiobook enhances the written work.